Propagation Control of Octahedral Tilt in SrRuO3 via Artificial Heterostructuring. Issue 16 (25th June 2020) - Jeong, Seung Gyo; Han, Gyeongtak; Song, Sehwan; Min, Taewon; Mohamed, Ahmed Yousef; Park, Sungkyun; Lee, Jaekwang; Jeong, Hu Young; Kim, Young‐Min; Cho, Deok‐Yong; Choi, Woo Seok
Abstract: Bonding geometry engineering of metal–oxygen octahedra is a facile way of tailoring various functional properties of transition metal oxides. Several approaches, including epitaxial strain, thickness, and stoichiometry control, have been proposed to efficiently tune the rotation and tilt of the octahedra, but these approaches are inevitably accompanied by unnecessary structural modifications such as changes in thin‐film lattice parameters. In this study, a method to selectively engineer the octahedral bonding geometries is proposed, while maintaining other parameters that might implicitly influence the functional properties. A concept of octahedral tilt propagation engineering is developed using atomically designed SrRuO3 /SrTiO3 (SRO/STO) superlattices. In particular, the propagation of RuO6 octahedral tilt within the SRO layers having identical thicknesses is systematically controlled by varying the thickness of adjacent STO layers. This leads to a substantial modification in the electromagnetic properties of the SRO layer, significantly enhancing the magnetic moment of Ru. This approach provides a method to selectively manipulate the bonding geometry of strongly correlated oxides, thereby enabling a better understanding and greater controllability of their functional properties. Abstract : Propagation control of octahedral bonding geometry is established via atomic‐scale fabrication of artificial oxide superlattices. RuO6 octahedral distortion in SrRuO3 layers are systematically modulated by controlling the atomic unit cell thickness of adjacent cubic SrTiO3 layers, further stabilizing the macroscopic crystalline symmetry. The customized lattice degree of freedom provides selective controllability over the functionalities of the strongly correlated oxide.